2021
DOI: 10.1111/joop.12372
|View full text |Cite
|
Sign up to set email alerts
|

Stability and change in levels of work–family conflict: A multi‐study, longitudinal investigation

Abstract: There has been little theoretical and empirical attention to the role of time in studying levels of work–family conflict. Contrary to theoretical assumptions that work–family conflict is a highly dynamic construct, we borrow from established theories to describe a Stability and Change Model, which posits that work–family conflict levels are primarily stable with some meaningful change over time. The proposed model also outlines predictors of stability (and change) in work–family conflict levels: stability (or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 103 publications
1
54
0
Order By: Relevance
“…Specifically, recent mean correlations of rfalse¯ = .36 between work demands and WIF and rfalse¯ = .24 between family demands and FIW have been reported (Allen et al, 2020). In addition, studies suggest substantial within-person stability of WFC across time (e.g., Matthews et al, 2014; Rantanen et al, 2012; Smith et al, 2022).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, recent mean correlations of rfalse¯ = .36 between work demands and WIF and rfalse¯ = .24 between family demands and FIW have been reported (Allen et al, 2020). In addition, studies suggest substantial within-person stability of WFC across time (e.g., Matthews et al, 2014; Rantanen et al, 2012; Smith et al, 2022).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Although longitudinal models are powerful, conducting longitudinal research is expensive, time consuming, and logistically challenging. More importantly, research typically includes employees who are already established in their work and family roles—many of the processes linking factors such as role demands with conflict experiences are likely to have reached a level of equilibrium (Smith et al, 2022). Unless there are major shocks that occur during the course of the longitudinal study (e.g., change in employment; birth of a child), there may be little change in relevant constructs for panel models to detect (McArdle, 2009).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Longitudinal research suggests that individuals have relatively stable levels of WIF and FIW that endure over months and years (Cho et al, 2013; Cooklin et al, 2016; Hecht & McCarthy, 2010; Rantanen et al, 2012; Smith et al, 2021). Stable WIF and FIW levels are likely due to chronic dispositions and situations (Smith et al, 2021), akin to consistencies found in daily hassles over time (e.g., Chamberlain & Zika, 1990). Yet, the typical exclusive focus on adulthood experiences obfuscates our understanding of how these levels develop.…”
Section: Psychological Maltreatment and Levels Of Work–family Conflic...mentioning
confidence: 99%
“…A smaller set of recent studies, however, suggests work–family conflict has stable features as well. For example, longitudinal work suggests work–family conflict is relatively consistent on average across several years (e.g., Cho et al, 2013; Cooklin et al, 2016; Hecht & McCarthy, 2010; Rantanen et al, 2012; Smith et al, 2021). Studies with monthly assessment similarly show work–family conflict is highly correlated across waves (e.g., r ranges from .66 to .83 across 1-month lags in Matthews et al, 2014; see also Nohe et al, 2015 meta-analysis).…”
mentioning
confidence: 99%
See 1 more Smart Citation